2017
DOI: 10.1007/978-3-319-56802-7_15
|View full text |Cite
|
Sign up to set email alerts
|

Some Mobile Overconstrained Parallel Mechanisms

Abstract: The Griffis-Duffy platform is an example of an overconstrained parallel mechanism. Although it has 6 SS legs joining its platform to its base it is still mobile. In this work similar structures are found but with different types of legs. The key to finding these structures is a pair of theorems concerning 3 degree-of-freedom mechanisms subjected to a translation or a half-turn. Although these results are not new concise statements and proofs are given. These constructions are then applied to parallel mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The fourth joint must still remain in Π but now as Π moves we can see that 4 will remain in the special line complex with axis 1 . Note that this motion can be mechanically generated by a UPU linkage, see [8]. As mentioned in the previous section, the variety of rigid-body motions that keep a line in a fixed linear line complex is given by the intersection of the Study quadric with another quadric hypersurface.…”
Section: Fixed First Linkmentioning
confidence: 98%
“…The fourth joint must still remain in Π but now as Π moves we can see that 4 will remain in the special line complex with axis 1 . Note that this motion can be mechanically generated by a UPU linkage, see [8]. As mentioned in the previous section, the variety of rigid-body motions that keep a line in a fixed linear line complex is given by the intersection of the Study quadric with another quadric hypersurface.…”
Section: Fixed First Linkmentioning
confidence: 98%
“…Here, we reveal the axial symmetry more elegantly using commutativity of coaxial translation and rotation. We would like to draw a connection between this new approach and some recent work of Selig [26], where the role of commutativity in synthesis of several novel mechanisms is emphasized.…”
Section: Synthesis Condition Of N-uu Pmmentioning
confidence: 99%
“…Therefore, Eqn. (26) Comparison with the Collapsed N-UU PM In [15], we introduced a collapsed N-UU PM, where each leg is a spherical chain (w + i1 , w + i2 , w − 12 , w − 11 ), and moreover, w + i2 = w − 12 . When N = 3, we have shown that its constraint singularity is given by the following identity:…”
Section: Singularity Analysis Of N-uu Pms Leg Singularitymentioning
confidence: 99%